2022
DOI: 10.4103/ijo.ijo_2886_21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-concentration atropine eye drops on the optical quality of the eyes in myopic children

Abstract: Purpose: The present study was performed to compare the optical quality of the eyes of myopic children before and after treatment with atropine eye drops of different concentrations. Methods: In the study population of 71 patients (131 eyes), 34 patients (63 eyes) were given 0.01% atropine eye drops and 37 patients (68 eyes) were given 0.05% atropine eye drops. The modulation transfer function (MTF) cutoff frequency, Strehl ratio, objective scattering index (OSI), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…And, given the allergic reactions to the eyes, atropine eye drops is often given at a low dose to myopic children [ 11 ]. Studies have shown that 0.01% atropine eye drops (low-dose atropine (LDA)) has no significant adverse effects on children's optical quality, with better therapeutic safety than 0.05% atropine eye drops [ 12 ]. In terms of visual training, virtual reality (VR)-based binocular visual function (BVF) balance training is a kind of stereoscopic perception training for patients by wearing VR visual training glasses.…”
Section: Introductionmentioning
confidence: 99%
“…And, given the allergic reactions to the eyes, atropine eye drops is often given at a low dose to myopic children [ 11 ]. Studies have shown that 0.01% atropine eye drops (low-dose atropine (LDA)) has no significant adverse effects on children's optical quality, with better therapeutic safety than 0.05% atropine eye drops [ 12 ]. In terms of visual training, virtual reality (VR)-based binocular visual function (BVF) balance training is a kind of stereoscopic perception training for patients by wearing VR visual training glasses.…”
Section: Introductionmentioning
confidence: 99%